Biliary Tract Exploration After Laparoscopic Left-sided Hepatectomy: A Comparative Study of Left Hepatic Duct Orifice Versus Common Bile Duct Approach. Issue 5 (10th October 2022) - Tu, Shuju; Sun, Gen; Fang, Kang; Xin, Wanpeng; Zha, Ming; Wan, Renhua; Li, Yong; Xiao, Weidong
Abstract : Background: Laparoscopic left-sided hepatectomy (LLH) and additional biliary tract exploration are effective methods to treat left-sided hepatolithiasis (LSH) combined with extrahepatic bile duct stones. Although biliary tract exploration through common bile duct (CBD) incision has been widely accepted, the safety and effectiveness of the left hepatic duct (LHD) orifice approach after LLH is still in debate. Methods: One hundred and forty-four patients with LSH who underwent LLH and biliary tract exploration in our institution from April 2014 to September 2021 were enrolled in the retrospectively study. They were divided into 3 groups: LHD group (n=67), CBD/T-tube group (n=58), and CBD/PC group (n=19). Patients' demographic characteristics, intraoperative, and postoperative outcomes were retrospectively analyzed. Results: LHD group exhibited a shorter operative time (202.8±42.2 vs. 232.7±47.5 min, P =0.000), time to first bowel movement (2.3±0.5 vs. 2.9±0.7 d, P =0.000) and postoperative hospital stay (7.5±2.1 vs. 9.8±5.2 d, P =0.001) compared with the CBD/T-tube group. The lithotomy time in the LHD group was significantly longer than that in the CBD/T-tube group (33.6±7.3 vs. 29.0±6.3 min, P =0.000) and CBD/PC group (33.6±7.3 vs. 28.7±3.7, P =0.006). Intraoperative blood loss, blood transfusion rate, initial stone clearance rate, and stone recurrence rate all had no significant differences between the 3 groups (all P >0.05). LHD group showed less rate of electrolyte imbalance than that of the CBD/T-tube group (3.0% vs. 19.0%, P =0.004) but it was equivalent to the CBD/PC group ( P >0.05). The type of biliary tract exploration (odds ratio: 5.43, 95% confidence interval: 0.04-0.95, P =0.032) as independent predictors of electrolyte imbalance. No reoperation and mortality occurred in the 3 groups. The conversion rate was comparable among 3 groups (1.5% vs. 1.7% vs. 0, all P >0.05). No significant difference in stone recurrence rate was seen (1.5% vs. 3.4% vs. 0, all P >0.05). Conclusion: Biliary tract exploration through LHD orifice after LLH is a safe and effective treatment for selected patients with LSH, with an advantage over the T-tube drainage in the field of operative time, the incidence of electrolyte imbalance, recovery of gastrointestinal function, and postoperative hospital stay.